Living standards, poverty and inequality in the UK: 2013 - Jonathan Cribb; Andrew Hood; Robert Joyce; David Phillips (Institute for Fiscal Studies (IFS), 2013)
The official statistics on the distribution of income and the extent of poverty in the UK in 2011-12 were released on Thursday 13 June 2013. Using the data underlying these statistics, this report analyses: •the changes in average incomes in the most recent year of data and the period since the start of the 'Great Recession'; •how the gap between rich and poor has changed and how this differs when looking at pre-tax-and-benefit income rather than net income; •the recent changes in both relative and absolute income poverty for the whole population and among different parts of the population; •the striking long-term changes in incomes and poverty rates for different parts of the population and different age groups; •the prospects for average incomes, inequality and poverty in the years ahead.
Keywords: 330